Process modeling and analysis of service-oriented architecture–based wireless sensor network applications using multiple-domain matrix - Wen-Tin Lee; Shang-Pin Ma (International Journal of Distributed Sensor Networks)
The wireless sensor network represents distributed environment that consists of sensors and actuators to monitor and control real-world objects and devices. Web services and service-oriented architecture are fundamental elements to provide on-demand applications. The integration of business processes with wireless sensor network and service-oriented architecture will result in a better alignment of enterprise applications. This article uses multiple-domain matrix extensions called the business process model and notation–multiple-domain matrix to analyze structures of and relations among processes modeled in the business process model and notation with wireless sensor network elements and services. By applying an organization-activity multiple-domain matrix partitioning algorithm, different organizations and coupled activities with cyclic relations are identified to provide process structure information in a matrix perspective, which promote business process analysis and optimization. The partitioning analysis results can be used to form an initial software architecture which includes subsystems or packages so that the architecture-centric software engineering practice can be applied to help the development of wireless sensor network applications. Two process examples of wireless sensor network applications were used and analyzed for illustration and validation purposes.